2016
DOI: 10.1002/cctc.201600680
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Guided Redesign of CYP153AM.aq for the Improved Terminal Hydroxylation of Fatty Acids

Abstract: The structure of a P450 ω‐hydroxylase bound to its fatty acid product was determined, which revealed a narrow substrate tunnel that leads to the heme. The introduction of an arginine side chain in proximity to the carboxyl group of the fatty acid led to a reduced KM value for dodecanoic acid, which suggests the importance of an anchoring point in the active site. An increase in the flexibility of the substrate recognition region was also engineered, which resulted in a threefold improved product formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 45 publications
0
35
0
Order By: Relevance
“…Dodecanoic acid is predicted to interact with a similar set of residues: Leu92 (SRS1); Leu176 (SRS2); Phe238, Leu239, Val242, Ala243, Thr247 (SRS4); Ala290, Pro289 (SRS5) and Ile395 (SRS6). In such a predicted binding conformation the C7, C8, C9, C10 and C11 carbon atoms are most optimally located for hydroxylation ( Figure 6B [65], which are highly regioselective, display a narrow hydrophobic tunnel for binding FAs, restricting substrate motility in their active site. Likely, all in-chain FA hydroxylating P450s display similar active site properties as CYP267B1, explaining why so far no 'exclusive P450 in-chain hydroxylase' has been reported [52].…”
Section: Cyp267b1-tetradecanoic Acid Complex and Prediction Of Fatty mentioning
confidence: 99%
“…Dodecanoic acid is predicted to interact with a similar set of residues: Leu92 (SRS1); Leu176 (SRS2); Phe238, Leu239, Val242, Ala243, Thr247 (SRS4); Ala290, Pro289 (SRS5) and Ile395 (SRS6). In such a predicted binding conformation the C7, C8, C9, C10 and C11 carbon atoms are most optimally located for hydroxylation ( Figure 6B [65], which are highly regioselective, display a narrow hydrophobic tunnel for binding FAs, restricting substrate motility in their active site. Likely, all in-chain FA hydroxylating P450s display similar active site properties as CYP267B1, explaining why so far no 'exclusive P450 in-chain hydroxylase' has been reported [52].…”
Section: Cyp267b1-tetradecanoic Acid Complex and Prediction Of Fatty mentioning
confidence: 99%
“…In 2016, the structure of CYP153A from Marinobacter aquaeolei (CYP153A M.aq ) was solved with and without its 12-hydroxydodecanoic acid ligand. The authors found that CYP153A M.aq has terminal hydroxylase activity and that the A231G single mutation induced three-fold higher activity by increasing the flexibility of the substrate binding region [16]. Previous studies also demonstrated that Sphingomonas sp.…”
Section: Introductionmentioning
confidence: 99%
“…Such a strategy of modulating substrate specificity has been successfully demonstrated on various fatty acid utilizing enzymes in literature. [12] We also based the selection of some of our mutants on recent studies with FAP, where mutations were generally performed for other purposes than our aim here. The list of mutants and the purpose in their selection are given in Table 1.…”
Section: Selection Of Mutation Sitesmentioning
confidence: 99%